Identification of Inhibitors of Integrin Cytoplasmic Domain Interactions With Syk - Bakthavatsalam, Deenadayalan; Craft, John W.; Kazansky, Anna; Nguyen, Nghi; Bae, Goeun; Caivano, Amy R.; Gundlach, C. William; Aslam, Asra; Ali, Safa; Gupta, Shashikant; Lin, Sophie Y.; Parthiban, Hema D.; et al. (Frontiers in Immunology, 2021)
Leukocyte inflammatory responses require integrin cell-adhesion molecule signaling through spleen tyrosine kinase (Syk), a non-receptor kinase that binds directly to integrin β-chain cytoplasmic domains. Here, we developed a high-throughput screen to identify small molecule inhibitors of the Syk-integrin cytoplasmic domain interactions. Screening small molecule compound libraries identified the β-lactam antibiotics cefsulodin and ceftazidime, which inhibited integrin β-subunit cytoplasmic domain binding to the tandem SH2 domains of Syk (IC50 range, 1.02-4.9 µM). Modeling suggested antagonist binding to Syk outside the pITAM binding site. Ceftazidime inhibited integrin signaling via Syk but did not inhibit ITAM-dependent phosphorylation of Syk mediated by FcγRI signaling. Our results demonstrate a novel means to target Syk independent of its kinase and pITAM binding sites such that integrin signaling via this kinase is abrogated but ITAM-dependent signaling remains intact. As integrin signaling through Syk is essential for leukocyte activation, this may represent a novel approach to target inflammation.